Advertising, democracy and censorship - Craig, Robert L. (Javnost (Ljubljana), 2004)
The article develops an argument for the control of commercial and political advertising in the United States and a return to a journalism of public service and in support of democratic principles of communication. Based on a number of previous studies, the author describes and analyzes the impact of a business culture on the traditional role of the media, the expectations of journalism, and the rights of citizen to be informed by a range of ideas and in the spirit of a democratic existence.
Keywords: United States of America; ZDA; state; država; mass media; množični mediji; komuniciranje; communication; advertising; oglaševanje; informiranje; obveščanje; democracy; demokracija; svoboda tiska